4,4 `-(Propane-1,3-diyldioxy)dibenzaldehyde - Ali, Q.; Shah, M.R.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(17)H(16)O(4), is a dialdehyde in which two formylphenoxy units are linked by a-CH(2)CH(2)CH(2)- chain; the molecule is V-shaped with the middle methylene C atom as the apex. The two benzene rings are aligned at 77.4 (1)degrees. In the crystal, molecules are linked into centrosymmetric dimers by pairs of non-classical C-H center dot center dot center dot O hydrogen bonds.